2008
DOI: 10.2174/156720108783954842
|View full text |Cite
|
Sign up to set email alerts
|

Use of Microwave in Processing of Drug Delivery Systems

Abstract: Microwave has received a widespread application in pharmaceuticals and food processing, microbial sterilization, biomedical therapy, scientific and biomedical analysis, as well as, drug synthesis. This paper reviews the basis of application of microwave to prepare pharmaceutical dosage forms such as agglomerates, gel beads, microspheres, nanomatrix, solid dispersion, tablets and film coat. The microwave could induce drying, polymeric crosslinkages as well as drug-polymer interaction, and modify the structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 94 publications
0
29
0
Order By: Relevance
“…[38][39][40][41][42][43][44] The drug release property of an alginate matrix is strongly governed by the composition of the uronic acid sequences. [1,105,106] The mannuronic acid-rich alginate matrix gives lower drug release rates in dissolution medium of pH 1.2 but higher drug release rates at pH 6.8 when compared with guluronic acid-rich Beads [6,[64][65][66][67][68][69][70][71][72][73][74] Chitosan is introduced as chitosan membrane or directly as alginate-chitosan blend in alginate beads crosslinked by calcium chloride via ionotropic gelation method. The alginate-chitosan beads can be further crosslinked through reacting chitosan with sodium sulfate.…”
Section: Oral Drug Deliverymentioning
confidence: 99%
“…[38][39][40][41][42][43][44] The drug release property of an alginate matrix is strongly governed by the composition of the uronic acid sequences. [1,105,106] The mannuronic acid-rich alginate matrix gives lower drug release rates in dissolution medium of pH 1.2 but higher drug release rates at pH 6.8 when compared with guluronic acid-rich Beads [6,[64][65][66][67][68][69][70][71][72][73][74] Chitosan is introduced as chitosan membrane or directly as alginate-chitosan blend in alginate beads crosslinked by calcium chloride via ionotropic gelation method. The alginate-chitosan beads can be further crosslinked through reacting chitosan with sodium sulfate.…”
Section: Oral Drug Deliverymentioning
confidence: 99%
“…Microwave has been utilized to design controlled-release alginate, alginate-chitosan, pectinate-chitosan and poly(methyl vinyl etherco-maleic acid) beads [2][3][4][5]. The drug release characteristics of these beads were dependent on the propensity of polymer-polymer and drug-polymer interaction brought about by microwave.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the drug release propensity of microwave-treated sample is greatly higher than those of pure drug, samples which are untreated by microwave or treated by vacuum at 100 • C, or obtained by solvent deposition method. A review of microwave application in design of drug delivery system, namely agglomerates, beads, tablets, microparticles, nanoparticles and solid dispersion, has been reported lately by Wong (2008) [4].…”
Section: Introductionmentioning
confidence: 99%
“…The transmission of microwave to an object results in vibration of molecules by induced or permanent dipoles. The microwave technology has been used to design controlled release solid matrices of pectin, alginate, chitosan, poly(methylvinylether-co-maleic acid) and gelatin prepared by ionotopic gelation, coacervation and denaturation processes [3][4][5][6][7][8]. The drug release property of these solid matrices is modified through subjecting the formed products to microwave treatment in solid or liquid state.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics and mechanism of solid particle assembly are different from matrices formed via ionotropic gelation, coacervation and denaturation processes whereby the former produces spheroids via wetting of solid powder by binding liquid whereas the latter involves the transformation of polymer solution into solid polymeric matrices. Under the influence of microwave, the changes in interaction propensity between polymer and/or drug of an object is known to be affected by its physicochemical attributes which in turn are a function of its assembly conditions [8]. The ease of modifying drug release property of spheroids by microwave can be lower than matrices prepared by gelation, coacervation and denaturation methods as polymer and/or drug particles in a spheroid are assembled with a larger inter-particulate distance and their interaction propensity can be less inducible by microwave.…”
Section: Introductionmentioning
confidence: 99%